Bacillus licheniformis FMCH001 Increases Water Use Efficiency via Growth Stimulation in Both Normal and Drought Conditions - Akhtar, Saqib Saleem; Amby, Daniel Buchvaldt; Hegelund, Josefine Nymark; Fimognari, Lorenzo; Großkinsky, Dominik K.; Westergaard, Jesper Cairo; Müller, Renate; Moelbak, Lars; Liu, Fulai; Roitsch, Thomas (Frontiers in Plant Science, 2020)
Increasing agricultural losses due to biotic and abiotic stresses caused by climate change challenge food security worldwide. A promising strategy to sustain crop productivity under conditions of limited water availability is the use of plant growth promoting rhizobacteria (PGPR). Here, the effects of spore forming Bacillus licheniformis (FMCH001) on growth and physiology of maize (Zea mays L. cv. Ronaldinho) under well-watered and drought stressed conditions were investigated. Pot experiments were conducted in the automated high-throughput phenotyping platform PhenoLab and under greenhouse conditions. Results of the PhenoLab experiments showed that plants inoculated with B. licheniformis FMCH001 exhibited increased root dry weight and plant water use efficiency compared to uninoculated plants. In greenhouse experiments, root and shoot dry weight significantly increased by more than 15% in inoculated plants compared to uninoculated control plants. Also, the water use efficiency increased in FMCH001 plants up to 46% in both well-watered and drought stressed plants. Root and shoot activities of 11 carbohydrate and 8 antioxidative enzymes were characterised in response to FMCH001 treatments. This showed a higher antioxidant activity of catalase in roots of FMCH001 treated plants compared to uninoculated plants. The higher catalase activity was observed irrespective of the water regime. These findings show that seed coating with gram positive spore forming B. licheniformis could be used as biostimulants for enhancing plant water use efficiency under both normal and drought stress conditions.